Development of the digital human resource training platform for women employees - S., Safrida; Budhiartini, Dewi; S., Supriadi; Zenni, Riana; Y., Yusrita (2025)
This study aims to develop a Digital Women’s Human Resource Development Training Platform at the Islamic University of North Sumatra (UISU). This platform is called the Digital Women’s Human Resource Development Training Platform (P3SPD) in Indonesian. This platform is designed as a webbased medium to support the improvement of digital competencies among female staff in academic environments. This study adopted a mixed-methods approach, combining qualitative and quantitative methods based on the Borg & Gall and Lee & Owens frameworks. The study population consisted of all 35 female staff members across 9 faculties at UISU, and a saturated sample of equal size was used. The research procedure involved nine stages, including digital needs analysis, planning, platform development, and effectiveness testing. The needs analysis revealed that although basic digital skills were adequate, participation in training was still low and needed to be improved, particularly regarding women’s involvement in decision-making and career development. The P3SPD platform was developed to address these challenges through a digital curriculum design, interactive features, and an integrated evaluation system. Initial trials showed very positive results, with an average score of 4.46. These findings indicate that the P3SPD platform has strong potential to support digital transformation and empower female employees at UISU.